Implementation Framework of ISO 22000 Food Safety Management System in Higher Educational Institutes (HEIs) Cafes of Pakistan - Shehzadi, S.; Wasim, A.; Hussain, S.; Shafiq, M.; Jahanzaib, M. (The Nucleus, 2019)
The purpose of this paper is to develop an implementation framework of ISO 22000 FSMS in Higher Educational Institutes (HEIs) cafes of Pakistan under the requirements of ISO standard. The framework has been developed based on the requirements of ISO 22000 food safety management system (FSMS). A total number of 30 HEIs cafes were analyzed through self-observations and face-to-face interviews with the managers of these cafes. The main part of the questionnaire comprises 41 questions about plan, 66 questions about do, 3 questions about check and 6 questions about act section. The findings of this research show that no cafe has been found to follow ISO 22000: 2005 FSMS requirements. Regarding status, 13% (4) of the cafes were found in poor while 86% (26) at moderate level. None of these cafes had Hazard Analysis Critical Control Point (HACCP) system and documentation related to any point. The prerequisite programs (PRPs) were found good in cleaning and sanitation, and layout of the premises. However, PRPs were weak in training and documentation. HEIs cafes should be more focused and interested towards the implementation of ISO 22000 standard requirements to provide safe food to students and staff. In conclusion, the proper implementation of prerequisite programs (PRPs) can help organizations to lead implementation of HACCP system. Providing proper training and knowledge related to food safety practices will be helpful for the organizations to provide safe and quality food to customers.